Rufus Rivers and career choices in private equity and venture capital finance - Rogers, Steve (Steven); Vaccaro, Pat; Whitaker, Scott T. (London : SAGE Publications Ltd, 2017)
Rufus Rivers, managing director and co-head of mezzanine investing at The Carlyle Group, is reviewing two employment offers he recently received. One came from RLJ Equity Partners, a private equity firm headquartered in the metropolitan Washington, D.C., area. The other came via Glocap Search, a New York-based executive search firm specializing in placing top private equity executives in premier venture capital roles. The Glocap recruiter had told Rivers that he had been selected as the leading candidate for a position with an established Boston-area venture capital firm that had several exciting investment prospects. In the next few days, Rivers needs to consider his personal and professional interests and make a decision: Should he go to Washington, go to Boston, or stay put and on what terms?
Originally published in Rogers, S., Vaccaro, P., & Whitaker, S. (2010). Rufus Rivers and Career Choices in Private Equity and Venture Capital Finance. 5-210-252. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Venture capital -- Vocational guidance; Private equity -- Vocational guidance; Career development